The Institutional Capacity Building of Al-Ittifaqiah Islamic Boarding School Based on Entrepreneurship - Yunindyawati Yunindyawati; Eva Lidya; Lili Erina; Tri Agus Susanto (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
This study aims to analyze Islamic boarding schools’ institutional capacity building to improve entrepreneurship among students. The method used is mixed. The data were collected through in-depth interviews. Observations are made by observing the daily activities of the boarding school in carrying out its roles and functions. The results of this study indicate that the institutional capacity building is carried out in a long and continuous. Normatively, it is arranged in the vision and mission and practically through various program activities that encourage the implementation of the vision and mission of the Islamic boarding school. Efforts to develop the institutional capacity of the cottage institutions are carried out by developing the ability of life skills, talents and potential based on the conditions and situations of the boarding school and students. Islamic boarding schools also carry out socio-economic adaptations in line with global developments and the digital era.